Investigation of Differentiated Instruction Model ESP Based on Students’ Needs at Vocational High School in Palembang - Irawan, Dodi; Sulistiyo, Urip; Abrar, Mukhlash (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study investigates the application of differentiated instruction (DI) models in English for Specific Purposes (ESP) classrooms at vocational high schools in Palembang, focusing on students’ linguistic and vocational needs. Using a systematic literature review (SLR) following PRISMA guidelines, the research analysed 15 articles from Scopus, ERIC, Google Scholar, and Web of Science. The findings reveal that DI strategies are inconsistently applied, with teachers often facing challenges due to large class sizes, insufficient training, and resource limitations. However, when implemented effectively, DI has been shown to improve student engagement and learning outcomes. The study identifies best practices for enhancing DI in vocational ESP settings, emphasizing the need for curriculum alignment, task variety, and professional development to address the unique needs of vocational students. Recommendations include providing ongoing teacher training and better resources to optimize DI models in such contexts.